The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.21608/ejbo.2019.6242.1248
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Immobilization of A Novel Hyaluronidase Produced By Streptomyces roseofulvus

Abstract: M AXIMUM hyaluronidase production by Streptomyces roseofulvus S10 (LC314796) was attained when it was cultured in submerged fermentation process under favorable conditions, pH 5 at 40ºC for 6 days. Hyaluronidase was purified to its homogeneity by 9.2 fold with molecular weight of 97kDa under denaturing SDS-PAGE. Mg +2 exerted highly stimulatory effect on S. roseofulvus S10 hyaluronidase activity and was significantly reduced in presence of Mn +2 , Zn +2 , and EDTA. Optimum reaction was attained at pH 9 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It well known that alginate present as gel beads in the medium but during fermentation carbon dioxide which produced by yeast cells caused the formation of cracks and capillaries in the alginate hydrogel, thus reducing the diffusion limit and so the transport of nutrients and metabolites is facilitated through the created structures using capillary forces (Poreda et al, 2011). In contrast Reda & Shanawany (2020) revealed that the maximum hyaluronidase enzyme immobilization yield (67.2%) was observed with Ca-alginate followed by agar-agar and Silica gel respectively. inoculum size of S. cerevisiae immobilized on wheat straw in continuous fermentation culture using a mixture of Egyptian cane and beet molasses with 16% initial sugar at 30 °C and pH4.5.…”
Section: Resultsmentioning
confidence: 83%
“…It well known that alginate present as gel beads in the medium but during fermentation carbon dioxide which produced by yeast cells caused the formation of cracks and capillaries in the alginate hydrogel, thus reducing the diffusion limit and so the transport of nutrients and metabolites is facilitated through the created structures using capillary forces (Poreda et al, 2011). In contrast Reda & Shanawany (2020) revealed that the maximum hyaluronidase enzyme immobilization yield (67.2%) was observed with Ca-alginate followed by agar-agar and Silica gel respectively. inoculum size of S. cerevisiae immobilized on wheat straw in continuous fermentation culture using a mixture of Egyptian cane and beet molasses with 16% initial sugar at 30 °C and pH4.5.…”
Section: Resultsmentioning
confidence: 83%
“…In order to purify the hyaluronidase from crude filtrate, the enzyme filtrate was firstly precipitated using 70% saturation ammonium sulfate solution as recommended by Reda & El-Shanawany [ 16 ]. The protein precipitate was dissolved using a 50 mM phosphate buffer (pH 7) and dialyzed three times using the same buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The co-expression of udgA and hasA genes from S. zooepidemicus results in a sharp decrease in the amount of product [143] . Unlike the hyaluronidase from streptococci, the activity of the hyaluronidase from Streptomyces roseofulvus S10 (LC314796) rises markedly in the presence of Mg 2+ , but decreases in the presence of Mn 2+ and Zn 2+ ions [290] .…”
Section: Production Of Ha With Other Gram-positive Bacteriamentioning
confidence: 99%